677.051 IMPACT OF SAW SPACING ON LINT REMOVAL EFFICIENCY AND QUALITY IN THE LINTING PROCESS - Tuychiyev, Sherzodbek; Madrahimov , Dilshodbek (Scientific and Technical Journal of Namangan Institute of Engineering and Technology, 2024)
This article presents the results of experimental studies conducted in laboratory conditions to investigate the impact of the saw spacing in linting equipment, enhanced with a working gin chamber, on the performance of lint removal and the quality of the obtained lint and lintered seeds. The experiments focus on how different saw intervals affect the productivity and the quality of both the lint and the lintered seeds.